Recalling word lists reveals “cognitive dysmetria” in schizophrenia: a positron emission tomography study. - Crespo-Facorro, Benedicto; Paradiso, Sergio; Andreasen, Nancy C. (American Journal of Psychiatry, 1999)
|WbObjective:[|WB] This study explored the neural circuitry used during recall of unstructured verbal material in schizophrenic patients and healthy volunteer subjects. |WbMethod:[|WB] The subjects were 13 healthy volunteers and 14 schizophrenic patients. All patients were free of medication, and all subjects were right-handed. Two experimental cognitive conditions were used: recall of novel and practiced word lists (two 15-item lists from the Rey Auditory Verbal Learning Test). Both active recall tasks were compared with an eyes-closed resting baseline condition. A nonparametric randomization test was used to determine within- and between-group differences in regional cerebral blood flow. |WbResults:[|WB] Performance on both the practiced and novel memory tasks was nonsignificantly different in the patients and control subjects. During the novel memory task, the patients showed decreased flow in the right anterior cingulate, right thalamus, and bilateral cerebellum (left greater than right) relative to the control subjects. When recalling the practiced word lists, the patients showed decreased flow in the left dorsolateral prefrontal cortex, bilateral medial frontal cortex, left supplementary motor area, left thalamus, left cerebellar regions, anterior vermis, and right cuneus. |WbConclusions:[|WB] Patients with schizophrenia fail to activate cortical-cerebellar-thalamic-cortical circuitry during recall of both well-learned and novel word lists. Reprinted by permission of the publisher.